Pengaruh Perssepsi Dukungan dan Keadilan Organisasi terhadap Organizational Citizenship Behavior dengan Komitmen Organisasional sebagai Variabel Intervening (Management Analysis Journal, 2015)
The study population was a nurse inpatient Islam Sultan Agung Hospital Semarang with a sample of 160 respondents from the formula slovin using purposive sampling method. Methods of data collection using questionnaires that measured using a Likert scale. Based on the partial test, the direct influence of perceived organizational support, justice and organizational commitment on organizational citizenship behavior amounted to 0.799; 0,072 and 0,000. Direct influence perceptions of support and justice organization on organizational commitment of each of 0001 and 0000. While the mediating effect organisional commitments on support and influence perceptions of organizational justice organizational citizenship behavior toward each are 0.178 and 0.314. The conclusions of this study there was no influence perceived of organizational support and organizational justice on organizational citizenship behavior. There is the influence of organizational commitment on organizational citizenship behavior. There is a direct direct effect of perceived organizational support and organizational justice on organizational commitment. Proven organizational commitment has mediating effects of perceived organizational support and organizational justice on the organizational citizenship behavior